An investigation into the use of L1 in EFL classes in the Kurdistan region of Iraq - Khoshnaw, Sangar Ismail Hamed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
The present study aimed to identify the attitudes of students and teachers toward the use of L1 (Kurdish) in English as a foreign language (EFL) classes in basic and high schools in the city of Erbil in the Kurdistan Region of Iraq. It also investigated if attitudes of the learners change across different levels of study and gender. Besides, it tried to find out the students’ and the teachers’ perceived needs for L1 use in their classes. Finally, it looked into the students’ and the teachers’ actual uses of L1 to see when, where, and for what purposes they use it and to identify whether level of study and gender affect the students’ use of Kurdish. This research study was designed as a case study in which qualitative and quantitative methods of data collection were employed. The participants included 98 students and 4 teachers from 7th grade and 11th grade classes. The data was collected through a student questionnaire, a teacher questionnaire, teacher interviews, and classroom observations. The results of the study showed that the teachers and students were positive toward the use of Kurdish in English classes. However, the students were more positive than the teachers. While students believed that Kurdish can often be used in English classes, the teachers preferred moderate and sometimes use of it. The results also showed that the attitudes of 11th grade students were more positive than those of 7th grade students and that the difference between them was statistically significant. Similarly, the female students showed more positive attitudes than the male students did toward the use of Kurdish; yet, the difference was not statistically significant. It was found that the teachers use Kurdish usually because the students’ proficiency level was not adequate to understand English-only classes. Moreover, they thought it helps students understand and learn better, it helps teaching new vocabulary and difficult topics, and it saves time. Students reported that they use Kurdish because they think they are not proficient in English enough to speak it and it helps them understand and learn English. The results of the classroom observations showed that teachers and students used Kurdish extensively in different situations and for a variety of purposes while very little English was used by them. Finally, the findings showed that 11th grade students used much more L1 than 7th grade students did and that male students used more Kurdish than female students did. However, the difference between males’ and females’ use of Kurdish was not very considerable. In the light of the findings of the study, some pedagogical implications for a judicious and moderate use of L1 and implications for further research were proposed. Keywords: student attitudes, teacher attitudes, L1 (Kurdish), L2 (English), use of L1, gender, level of study

ÖZ: Bu çalışma, Irak Kürdistan Bölgesel Yönetimi’nin Erbil şehrinde bulunan ortaokul ve liselerdeki yabancı dil olarak İngilizce sınıflarında anadil (Kürtçe) kullanımına yönelik öğrencilerin ve öğretmenlerin tutumlarını belirlemeyi hedeflemiştir. Ayrıca, bu araştırma öğretmenlerin ve öğrencilerin söz konusu sınıflarda anadil kullanımı ile ilgili algısal ihtiyaçlarını da bulmayı amaçlamıştır. Bunlara ek olarak, öğrencilerin tutumlarının sınıf seviyesi ve cinsiyete bağlı olarak değişip değişmediği de incelenmiştir. Son olarak, ne zaman, nerede ve hangi amaçlar için Kürtçe kullanıldığını ve bunun sınıf seviyesine ve cinsiyete bağlı olarak değişip değişmediğini görmek için öğrencilerin ve öğretmenlerin sınıftaki gerçek anadil kullanımlarına bakılmıştır. Bu araştırma nitel ve nicel yöntemlerin kullanıldığı bir olgu çalışması olarak tasarlanmıştır. Katılımcılar, 7. ve 11. sınıflardan toplam 98 öğrenci ve dört öğretmenden oluşmaktadır. Çalışmanın verileri öğrenci anketi, öğretmen anketi, öğretmen mülakatları ve sınıf gözlemleri yoluyla toplanmıştır. Çalışmanın sonuçları, öğretmenlerin ve öğrencilerin İngilizce sınıflarında Kürtçe kullanımına karşı tutumlarının olumlu olduğunu göstermiştir. Ancak, öğrencilerin tutumları öğretmenlerinkine göre daha olumludur. Öyle ki, öğrenciler İngilizce sınıflarında sık sık Kürtçe kullanılabileceğini düşünürken, öğretmenler ölçülü bir şekilde, bazen kullanılmasını tercih etmişlerdir. Öğretmenlerin genellikle Kürtçe’yi öğrencilerin dil seviyelerinin yalnız-İngilizce olan dersleri anlamaya yetmeyeceği için kullandıkları da tespit edilmiştir. Ayrıca öğretmenler, anadil kullanımının öğrencilerin daha iyi anlamalarına ve öğrenmelerine katkı sağladığını, yeni kelimelerin ve zor konuların öğretilmesine yardımcı olduğunu ve zaman kazandırdığını düşündüklerini ifade etmişlerdir. Öğrenciler ise, İngilizce seviyelerinin bu dili konuşmaya yeterli olmadığını düşündükleri ve anadil kullanımının İngilizce’yi anlama ve öğrenmelerine yardımcı olduğuna inandıkları için Kürtçe kullandıklarını bildirmişlerdir. Ayrıca, çalışmanın sonuçları 11. sınıf öğrencilerinin tutumlarının 7. sınıf öğrencilerinin tutumlarından daha olumlu olduğunu göstermiştir. Bu farklılık istatistiksel olarak da önemlidir. Aynı şekilde, kız öğrencilerin Kürtçe kullanımına karşı tutumları erkek öğrencilerin tutumlarından daha olumludur. Fakat, bu farklılık istatistiksel olarak anlamlı değildir. Sınıf gözlemlerinin sonuçları ise öğretmenlerin ve öğrencilerin farklı durumlarda çeşitli amaçlarla yaygın bir şekilde Kürtçe kullandıklarını ve İngilizcenin çok az kullanıldığını ortaya koymuştur. Son olarak, 11. sınıf öğrencilerinin 7. sınıf öğrencilerinden, erkek öğrencilerin de kız öğrencilerden daha fazla anadil (Kürtçe) kullandıkları görülmüştür. Ancak, kız ve erkek öğrenciler arasındaki farklılık çok fazla dikkate alınacak bir farklılık değildir. Çalışmanın bulguları ışığında, anadilin makul (akıllıca) ve ölçülü olarak kullanılması için bazı sezdirimler ve ileriki çalışmalar için bazı öneriler sunulmuştur. Anahtar kelimeler: öğrenci tutumları, öğretmen tutumları, anadil (Kürtçe), ikinci dil (İngilizce), anadil kullanımı, cinsiyet, sınıf seviyesi
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2014. Supervisor: Assist. Prof. Dr. Fatoş Erozan.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching; Student Attitudes; Teacher Attitudes; L1 (Kurdish); L2 (English); use of L1; Gender; Level Of Study